2010
DOI: 10.1174/113564010791304528
|View full text |Cite
|
Sign up to set email alerts
|

Niveles de comprensión de las tablas en alumnos de primaria y secundaria

Abstract: sión. Algunos autores han planteado que esos niveles se describen bien distinguiendo entre lo que sería leer los datos, leer entre los datos y leer más allá de los datos. Cada uno de esos niveles implicaría un mayor grado de dificultad para quienes están en proceso de aprender a interpretar gráficos. En este estudio se ha contrastado esa distinción para el caso de las tablas. Mediante un cuestionario de doce preguntas relativas a una tabla cuantitativa se ha examinado a una muestra de alumnos de 5º y 6º de pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
37

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 21 publications
1
13
0
37
Order By: Relevance
“…On the one hand, it is possible that the levels of the rubric's execution, with regard to the plot and theme criteria, are not well adapted to the students' level; or else they are not adequately functional for generating sufficiently specific revisions of text pieces. On the other hand, several studies have demonstrated the difficulties that the students encounter when interpreting tables and other external representation systems in school tasks (Gabucio, Martí, Enfedaque, Gilabert, & Konstantinidou, 2010). There is no doubt that the rubric's format is difficult for a Primary student to interpret given that it contains columns and rows that signify something different than what is usually associated with this type of representation.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it is possible that the levels of the rubric's execution, with regard to the plot and theme criteria, are not well adapted to the students' level; or else they are not adequately functional for generating sufficiently specific revisions of text pieces. On the other hand, several studies have demonstrated the difficulties that the students encounter when interpreting tables and other external representation systems in school tasks (Gabucio, Martí, Enfedaque, Gilabert, & Konstantinidou, 2010). There is no doubt that the rubric's format is difficult for a Primary student to interpret given that it contains columns and rows that signify something different than what is usually associated with this type of representation.…”
Section: Discussionmentioning
confidence: 99%
“…These data on graph interpretation were gathered simultaneously with the data on graph construction by randomly splitting the classes into three subgroups: the first group of participants was assigned to Study 1, the second to Study 2 and finally, the third to a table interpretation task. Thus, with this extra set of data (Gabucio, Marti, Enfedaque, Gilabert, & Konstantinidou, 2010),…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred students were given a test in which they were asked to interpret a Gabucio, et al, 2010, name deleted to maintain the integrity of the review process for the interpretation test).…”
Section: Resultsmentioning
confidence: 99%
“…Los resultados muestran que los estudiantes trabajan y consideran aspectos de lectura literal de información, alcanzando con facilidad por estudiantes de primeros cursos de Educación Prima-ria, tal como lo confirman las investigaciones previas (e.g., ESPI-NOZA, 2015;GABUCIO et al, 2010;OCHOA, 2015;PEREIRA;CONTI, 2012).…”
Section: Discusión Y Conclusiónunclassified